Multidisciplinary screening of toxicity induced by silica nanoparticles during sea urchin development. (November 2015) - Gambardella, Chiara; Morgana, Silvia; Bari, Gaetano Di; Ramoino, Paola; Bramini, Mattia; Diaspro, Alberto; Falugi, Carla; Faimali, Marco
Highlights: Sea urchin fertilization ability was not affected by SiO2 NPs exposure. A significant percentage of anomalies were observed and quantified in exposed samples. Altered expression of acetylated tubulin, ChAT and AChE was found in exposed samples. The multidisciplinary approach was able to verify SiO2 NP effects in the offspring. Abstract: The aim of this study was to investigate the potential toxicity of Silica nanoparticles (SiO2 NPs) in seawater by using the sea urchin Paracentrotus lividus as biological model. SiO2 NPs exposure effects were identified on the sperm of the sea urchin through a multidisciplinary approach, combining developmental biology, ecotoxicology, biochemistry, and microscopy analyses. The following responses were measured: (i) percentage of eggs fertilized by exposed sperm; (ii) percentage of anomalies and undeveloped embryos and larvae; (iii) enzyme activity alterations (acetylcholinesterase, AChE) in the early developmental stages, namely gastrula and pluteus. Sperms were exposed to seawater containing SiO2 NPs suspensions ranging from 0.0001 mg/L to 50 mg/L. Fertilization ability was not affected at any concentration, whereas a significant percentage of anomalies in the offspring were observed and quantified by means of EC50 at gastrula stage, including undeveloped and anomalous embryos (EC50 = 0.06 mg/L), and at pluteus stage, including skeletal anomalies and delayed larvae (EC50 = 0.27 mg/L). Moreover, morphological anomalies were observed in larvae at pluteus stage, by immunolocalizing molecules involved in larval development and neurotoxicity effects – such as acetylated tubulin and choline acetyltransferase (ChAT) – and measuring AChE activity. Exposure of sea urchins to SiO2 NPs caused neurotoxic damage and a decrease of AChE expression in a non-dose-dependent manner. In conclusion, through the multidisciplinary approach used in this study SiO2 NPs toxicity in sea urchin offspring could be assessed. Therefore, the measured responses are suitable for detecting embryo- and larval- toxicity induced by these NPs.